Near Real-Time Identification of Recent Human Immunodeficiency Virus Transmissions, Transmitted Drug Resistance Mutations, and Transmission Networks by Multiplexed Primer ID–Next-Generation Sequencing in North Carolina. (14th July 2020) - Zhou, Shuntai; Sizemore, Sabrina; Moeser, Matt; Zimmerman, Scott; Samoff, Erika; Mobley, Victoria; Frost, Simon; Cressman, Andy; Clark, Michael; Skelly, Tara; Kelkar, Hemant; Veluvolu, Umadevi; et al.
Abstract: Background: The identification of recent human immunodeficiency virus (HIV) 1 infections among people with new HIV diagnoses is important to both tailoring and assessing the impact of HIV-1 prevention strategies. Methods: We developed a multiplexed Primer ID–next-generation sequencing approach to identify recent infections by measuring the intrahost viral diversity over multiple regions of the HIV-1 genome, in addition to detecting drug resistance mutations (DRMs) and phylogenetically linked clusters. We summarize the field implementation of this all-in-one platform among persons with newly diagnosed HIV-1 by the North Carolina State Laboratory of Public Health in 2018. Results: Overall, recent infection was identified in 94 (35%) of 268 patients with new HIV diagnoses. People <30 years old, and people who inject drugs were more likely to have diagnoses of recent infection. The reverse-transcriptase region K103N was the most commonly detected DRM (prevalence, approximately 15%). We found a total of 28 clusters, and persons with recent infection were more likely to be cluster members than were those with chronic infections ( P = .03). Conclusions: We demonstrate the rapid identification of recent infection and pretreatment DRMs coupled with cluster analysis that will allow prioritization of linkage to care, treatment, and prevention interventions to those at highest risk of onward transmission. Abstract : We developed an all-in-one phylodynamics platform to detect recent human immunodeficiency virus (HIV) infection, drug resistance, and transmission networks using next-generation-sequencing from remnant HIV diagnostic tests. Of persons with new diagnoses, 35% were estimated to be recently infected, and clustered infections were frequent.